印尼汉语学习者专用动量词习得偏误研究 - Therenica, Nia (Journal of Maobi, 2025)
This research explores the challenges Indonesian learners face in acquiring Chinese "momentum words," such as “场, 遍, 番, 顿, 下, 趟, 回, 阵, 通, 次,” due to the one-to-many correspondence between Chinese momentum words and Indonesian quantifiers, along with different verb-matching rules. Momentum words refer to specific quantifiers in Chinese that pair with verbs to indicate frequency, duration, or repetition. The study investigates these issues through a questionnaire survey and error analysis to identify common mistakes and their causes. Findings show that learners frequently make errors such as misordering, misubstitution, and omission, primarily due to negative transfer from Indonesian. To address these issues, the paper suggests teaching strategies that gradually increase in complexity and emphasize comparing Chinese and Indonesian quantifiers. The research highlights the importance of understanding the matching rules for verbs and momentum words and cultivating effective learning strategies for Indonesian students.